SUSTAINABLE TOURISM: EXPLORATION OF THE POTENTIAL FOR HALAL TOURISM RETRIBUTION ON THE NORTH COAST OF MADURA - Nurul Herawati; Bambang Haryadi; Hanif Yusuf Seputro; syah, sultan (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
This aim of study is to explore the potential for regional levy revenue derived from halal tourism on the north coast of Madura Island. The uniqueness of this research lies in taking the object of research (halal tourism) after the COVID-19 pandemic. Population is a halal tourist attraction located on the north coast of Pamekasan Regency and Sumenep Regency (Madura Island), namely Jumiang Beach, Lombang, E-Kasoghi, Talang Siring, and Slopeng. Data collection techniques using purposive sampling methods with time vulnerability during 2019 to 2022 which are processed using halal potential analysis methods and quantitative descriptive methods. The results showed that the potential revenue of the halal tourism sector of the Madura coastal coast is quite high, as seen from several destinations that are able to generate significant revenue. The high revenue potential on these beaches has implications for significant local native income opportunities or potential. This research contributes to the government's program in levying levies on halal tourism. This research also contributes to the application of economic theory, legal theory, political theory, interest theory, stakeholder theory, and sustainable development goals (SDGs) that support levy collection in the field of halal tourism.